PROFIL MAHASISWA DALAM PROSES STUDI DI UPI KAMPUS TASIKMALAYA - Rusmana, Nandang; Rahman, Taopik; Lestari, Tri (JURNAL PAUD AGAPEDIA, 2017)
This research is based on the academic problem which is the studentsâ€™ obstacle or difficulty in planning, implementing and maximizing the learning development. By taking the case in UPI Campus Tasikmalaya, there are some academic problems faced by the students. In this study the samples taken are students from level two, three and four majoring in PGSD and PGPAUD with total of 210 students. This research uses descriptive research method with reference to the following steps: (1) conducting a pre-emptive survey to reveal empirical data about the number of students experiencing non-success in learning; (2) conducting documentation and survey studies to obtain biographical data, activities outside the lecture, attitudes, studying habits and learning skills; (3) conducting quantitative analysis of the data to obtain a description of the relationships and differences among the variables studied; (4) formulatingthe strategies oflearning guidance for students who are unsuccessful in learning based on biographicaldata, activities outside the lecture, attitudes, studying habit and learning skill. The results obtained from the data profiles of students in the study process are210 students as much as 59% or 125 successful and as many as 66 students or 31% has not been successful. Based on data on average learning skill enough. As well as data on attitudes and study habits on average is enough. Form of guidance for students who have not been successful in the form of academic, personal or career guidance. Working closely with the student's Academic Advisor.Â Penelitian ini didadasarkan pada problema akademik yang merupakan hambatan atau kesulitan yang diperoleh para mahasiswa dalam merencanakan, melaksanakan dan memaksimalkan pengembangan belajarnya. Dengan mengambil kasus pada UPI Kampus Tasikmalaya beberapa problema akademik yang dihadapi para mahasiswa. Dalam penelitian ini sampel yang diambil adalah mahasiswa tingkat dua, tiga dan empat jurusan PGSD dan PGPAUD yang totalnya berjumlah 210 mahasiswa. Penelitian ini menggunakan metode penelitian deskriptif dengan mengacu kepada langkah-langkah sebagai berikut : (1) melakukann survey pendahuluaan untuk mengungkap data empirik tentang besarnya jumlah mahasiswa yang mengalami ketidakberhasilan dalam belajar; (2) melakukan studi dokumentasi dan survey untuk mendapatkan data biografis, aktivitas di luar kuliah, sikap dan kebiasaan belajar dan keterampilan belajar; (3) melakukan analisis kuantitatif terhadap data yang diperoleh untuk mendapatkan deskripsi tentang tata hubungan dan perbedaan di antara variabel yang diteliti; (4) merumuskan strategi bimbingan belajar bagi mahasiswa yang mengalami ketidakberhasilan dalam belajarnya berdasrkan data, biografis, aktivitas di luar kuliah, sikap dan kebiasaan belajar dan keterampilan belajar. Diperoleh hasil berupa data profil mahasiswa dalam proses studi, yaitu dari 210 mahasiswa sebanyak 59% atau 125 berhasil dan sebanyak 66 mahasiswa atau 31% belum berhasil. Berdasarkan data tentang keterampilan belajar rata-rata cukup. Serta data tentang sikap dan kebiasaan belajar rata-rata cukup. Bentuk bimbingan untuk mahasiwa yang belum berhasil berupa bimbingan akademik, sosial pribadi atau karir. Bekerja sama dengan Pembimbing Akademik mahasiswa.